Digestive tolerance and postprandial glycaemic and insulinaemic responses after consumption of dairy desserts containing maltitol and fructo-oligosaccharides in adults - Respondek, F; Hilpipre, C; Chauveau, P; Cazaubiel, M; Gendre, D; Maudet, C; Wagner, A (European journal of clinical nutrition, 2014)
Background/objectives: To evaluate the short-term digestive tolerance and glycaemic response of several associations of maltitol and short-chain fructo-oligosaccharides (scFOS) used to replace sugars (for example, dextrose) in foods. Subjects/methods: Thirty-six healthy subjects aged 18–60 years were recruited for the study and 32 completed it. The subjects consumed six different mixtures of dextrose, maltitol and scFOS added in a chocolate dairy dessert at a dosage of 35 g. The test days were separated by 2-week washout periods. The subjects reported the intensity of four individual gastrointestinal (GI) symptoms, number of bowel movements and stool frequency for the 48 h following consumption of the dessert. A subgroup of 18 subjects also provided blood samples 2 h after intake to evaluate the postprandial glycaemic and insulinaemic responses. Results: The composite score calculated from the intensity of flatulence, borborygmi, bloating and discomfort was significantly higher ( P <0.0001) for all the desserts containing maltitol and/or scFOS than for the control dessert containing dextrose, but remains at the level of mild effects. The number of bowel movements was also slightly increased ( P =0.0006) and the stools were softer ( P =0.0045) for the first 24 h but not after ( P =0.1373 and 0.5420, respectively). Blood glycaemic and insulinaemic responses were lower for all the sugar-free recipes containing maltitol and scFOS in comparison to the control one ( P <0.0001). Conclusions: This study has shown that maltitol and scFOS can be used jointly when formulating sugar-free foods with the benefit to lower postprandial glycaemic response with only a small and transient increase in non-serious GI symptoms.